CRACKING CONCRETE EFFECT ON THE RATE OF CHLORIDE DIFFUSION AND PERMEABILITY - Huda, Khoirul
This research studies the correlation between chloride diffusion coefficient in concrete obtained from the field, chloride diffusion coefficient obtained from salt ponding test method, and concrete permeability obtained from rapid chloride permeability test (RCPT). The field data used are the chloride concentrations in concrete from Muara Jati Port and Pelita II Port owned by PT Pelabuhan Indonesia II, and also PT Cirebon Power Port, which are calculated using Fick’s second Law. Concretes with strength K-250, K-400, and K-400 added 30% fly ash, was made to compare the effect of strength differences and the addition of fly ash to concrete durability against chloride rate. The concretes are conditioned using the feedback controlled splitting test method, so that the concretes are in the cracked condition on the scale of 200 ?m, 400 ?m, 600 ?m, and 800 ?m, and compared with the uncracked concretes. The results of the study shows that there is a real correlation between RCPT and salt ponding test results, but it becomes weak if fly ash is added. Salt ponding test can be used as a method to predict chloride concentration value because it is able to approach the value obtained from the field data. While RCPT results can be used if the correlation between RCPT and salt ponding test is known. Except for the concretes added with fly ash, salt ponding test is the recommended method. On the cracked concretes, RCPT results show that the greater the crack, the greater the permeability value. The use of fly ash and or stronger concretes will decrease the permeability value. However the concretes that are cracked with the sample dimensions following AASHTO T259 and ASTM C1543 are not suitable to be tested using salt ponding test method.